PENGARUH PERTUMBUHAN PERUSAHAAN, PERTUMBUHAN PENJUALAN DAN STRUKTUR AKTIVA TERHADAP STRUKTUR MODAL (Studi Empiris Pada Perusahaan Jasa Konstruksi Dan Bangunan yang terdaftar Di Bursa Efek Indonesia Periode 2013-2017) - Yulian, Tri Nurindahyanti; Rahman, Kristanti; Aprilia, Astika Mega (JURNAL EKONOMI, 2020)
The purpose of this research is to analyze the growth of the company, the growth of sales and the structure of the company's assets on the capital structure. The object of research is all construction and building service companies totaling 16 companies, as a sample of only 9 companies with the observation period 2013-2017. Independent variables are company growth, sales growth, and asset structure, while the dependent variable is the capital structure (debt to total asset ratio). Data analysis using multiple linear regression. These results indicate that the growth of the company does not affect the capital structure, sales growth does not affect the capital structure and asset structure affect the capital structure. Key Words : Asset Growth, Sales Growth, Structure Asset, Capital Structure